Design and Analysis of a Linear Hybrid Excitation Flux-Switching Generator for Direct Drive Wave Energy Converters. (22nd October 2013) - Huang, Lei; Hu, Minqiang; Liu, Jing; Liu, Chunyuan; Zhong, Weibo
Abstract : Linear generators have the advantage of a simple structure of the secondary, which is suitable for the application of wave energy conversion. Based on the vernier hybrid machines (VHMs), widely used for direct drive wave energy converters, this paper proposes a novel hybrid excitation flux-switching generator (LHEFSG), which can effectively improve the performance of this kind of generators. DC hybrid excitation windings and multitooth structure were used in the proposed generator to increase the magnetic energy and overcome the disadvantages of easily irreversible demagnetization of VHMs. Firstly, the operation principle and structure of the proposed generator are introduced. Secondly, by using the finite element method, the no-load performance of the proposed generator is analyzed and composed with ones of conventional VHM. In addition, the on-load performance of the proposed generator is obtained by finite element analysis (FEA). A dislocation of pole alignments method is implemented to reduce the cogging force. Lastly, a prototype of the linear flux-switching generator is used to verify the correctness of FEA results. All the results validate that the proposed generator has better performance than its counterparts.